EVALUASI PENGELOLAAN LIMBAH MEDIS PADAT DI RUMAH SAKIT X KABUPATEN GRESIK, JAWA TIMUR, INDONESIA - Elyana Agustini; Widya Nilandita; Rhenny Ratnawati; Shinfi Wazna Auvaria (Jurnal Ecocentrism, 2026)
X Hospital in Gresik Regency is a hospital that generates a significant amount of solid medical waste. Solid medical waste has the potential to pollute the environment and pose health risks if not managed properly. This study aims to identify and evaluate the solid medical waste management system implemented at X Hospital in Gresik. The research method used is descriptive, including observation, documentation, and interviews, using secondary data regarding the existing conditions of hazardous and toxic (B3) waste generation and the Standard Operating Procedures for B3 waste management in effect at X Hospital. Data analysis was carried out with reference to the Regulation of the Minister of Health of the Republic of Indonesia Number 2 2023, the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number 56 2015, and Government Regulation Number 22 2021. The results indicate that medical waste originates from almost all hospital service installations, categorized as infectious, sharp, and non-infectious waste. The amount of infectious waste from January to April 2025 reached 23,697.5 kg, while non-infectious waste amounted to 8,341 kg. The management system includes sorting, packaging, internal transportation, temporary storage, treatment, and collaboration with third parties. Solid medical waste management at Hospital X has been carried out quite well in accordance with applicable regulations.